Efektivitas Konseling Kelompok Cognitif Behavior Teraphy untuk Mengurangi Kecanduan Judi Online pada Remaja di Desa Pasarbatang. - Rifaldi Fajri Isnan; Akhmad Fajar Prasetya (Lembaga Pengembangan Kinerja Dosen, 2024)
Online gambling is a type of gambling that is carried out via the internet using electronic devices such as computers, laptops, tablets or cellphones. Included in these activities is betting money on various games or sporting events, both virtual and real. There are many impacts, one of which is addiction. Therefore, social support from friends and relatives is really needed by victims of online gambling addiction. This research uses a quantitative approach, the method used in this research is quasi-experimental, with a non-equivalent control group design. Determining subjects used purposive sampling technique. The subjects of this research were 12 teenagers from Pasarbatang village who were divided into six teenagers in the experimental group and six teenagers in the control group. The data collection technique used is the online gambling addiction behavior scale. Validity test and reliability test using SPSS 23.0 Windows version.